PENGARUH VARIASI CAMPURAN OKSI-ASETILEN PADA PROSES FLAME HEATING TERHADAP SIFAT FISIS DAN MEKANIK ALUMINIUM SERI 7075 - Purnadityanto Purnadityanto; Teguh Triyono; Nurul Muhayat (Mekanika: Majalah Ilmiah Mekanika, 2019)
The optimum properties of aluminum can be achieved by the addition of alloy and heat treatment. An experimental study was conducted to investigate the effect of the oxy-acetylene mixture on the flame heating process on the physical and mechanical properties of aluminum 7075. Aluminum was heated to 480° C using an oxy-acetylene flame and then cooled rapidly. Then the results were compared with the specimen with flame heating + aging treatment. Variations of oxygen and acetylene mixtures were 0.75, 0.875 and 1 liter/min. The distance of the torch to the specimen's surface is 3 cm and the water flow rate is 1400 cc/min. The aging process is carried out with a temperature of 120°C for 3 hours + 165 for 1 hour. The results showed that the highest hardness value in flame heating treatment was 143,10 HVN with acetylene variation 0,875 liter/minute. The result of the impact test does not change much from the initial material toughness value, due to the average flame heating time that is not too long.